Short Videos as a Tool for Developing Intercultural Competence - Abetanov, Dias; Burdina, Elena; Kozhakhmet, Zhaksylyk (Journal of Education Culture and Society, 2026)
Aim. The aim of this study is to investigate the influence of Instagram Reels on the development of intercultural competence among university students. The research seeks to determine whether systematic exposure to short-form video content from diverse world regions can foster cultural awareness, empathy, and openness towards diversity. Methods. The experiment involved students, divided into five groups (10 participants in each group. Five of them experimental group, five of them control group), each exposed for ten consecutive days to a curated set of ten Reels per day. The videos represented five distinct cultural regions: the Balkans, South-East Asia, North Africa, Sub-Saharan Africa, and Central Asia. Diagnostic tools include: authors` developed questionnaire comprising 24 closed-ended and 5 open-ended questions and “Integrative Intercultural Competence Questionnaire”. Results. The findings demonstrate a notable increase in participants’ cultural awareness and readiness for intercultural engagement. Students reported improved recognition of cultural practices, stronger interest in interacting with foreign peers, and a reduced reliance on stereotypes. Quantitative data revealed that over 70% of participants expressed greater confidence in intercultural communication following the experiment. Conclusions. The study confirms the potential of Instagram Reels as an effective instrument for enhancing intercultural competence in educational settings. The accessibility, visual richness, and emotional appeal of the format make it a valuable tool for integrating cultural learning into students’ everyday media practices. Research restrictions. The relatively small sample size and limited duration of the experiment (10 days) restrict the generalisability of the findings. For the further research, we recommend larger cohorts and extended exposure periods. Practical application. The outcomes of this study may inform the development of digital education strategies designed to strengthen intercultural competence through the purposeful use of social media platforms. Originality. This research constitutes one of the first empirical attempts to explore Instagram Reels as a medium for intercultural education, highlighting the potential to bridge cultural divides and enrich internationalised learning environments.